Developing “learning society” as a basic condition for perfect management education in China - M. Yu. Zakharov; A. V. Shishkova (Вестник университета)
The article analyzes the Chinese educational system historical formation as an instrument of human capital development. Using the historical retrospection method and hermeneutic method, the authors, based on the works of ancient Chinese thinkers, study the development and formation of management education as a core element of the Chinese educational system. Turning to Chinese prognosticism, the authors take the image of the Great Unity society, that is, social justice and equal opportunities for all citizens (“Datong”) as a basis for the future desired image, which throughout centuries of Chinese history show the universal value of education and the high status of a civil servant in such a society. The historical background of modern educational system formation has been described and one of the key problems of modern China – the gap between the huge demand for higher education in society and the difficulties in the employment of graduates – pointed out. Conclusions have been drawn about the main features of the public administration modern system, the Chinese education place in the international market of educational services and the possible contribution of Chinese public administration researchers to the solution of public problems both within the country and around the world. Strategic scenarios for the further development of Chinese society in the context of the Datong project have been outlined.